Des villes et de la question multiculturelle : comment définir un espace multiculturel ? - Cynthia Ghorra-Gobin (Cybergeo, 1999)
Multiculturalism has been largely used in social science as well as by the media and the political debate, in the last few years. Although not very precise as a concept, it helps designate cities which include social groups which are culturally distinctive. Based on an analysis of the redistricting in Los Angeles, this text has an objective to underline the ambivalences of multiculturalism for not being able to give meaning to a public multicultural space.